All change: a stroke inpatient service's experience of a new clinical neuropsychology delivery model. Issue 1 (30th January 2019) - Boakye, Ndidi T; Scott, Richard; Parsons, Aisling; Betteridge, Shai; Smith, Melody A; Cluckie, Gill
Abstract : Adults presenting to stroke services are frequently faced with the challenge of adjusting to a different life following a stroke. Difficulties often include cognitive impairments, such as memory deficits, attention and language difficulties, and mood disturbances such as anxiety and depression. It has been highlighted that psychological care for this group is just as important as physical rehabilitation. Psychological expertise may therefore be required for the multitude of problems that occur after a stroke. UK National guidelines recommend routine assessment and management of mood and cognition after stroke. The aim of this study was to evaluate a new stroke clinical neuropsychology service developed by the Department of Neuropsychology and Clinical Health Psychology, in order to meet the needs of stroke survivors and their families referred into a large acute hospital. This involved using a different skill mix of staff across one post delivering a service in an acute inpatient stroke unit. This model was evaluated and results revealed that the model delivered increased patient access to neuropsychological support, an expansion in provision of clinical work, along with positive multidisciplinary team feedback. This finding is key as where resources are limited, clinical services may benefit from adopting a 'skill mix' model to meet the varying needs of their patients in a timely manner. This model serves to raise the value of psychology to medical services.